Waterlogging Affects Leaf and Tillering Dynamics in Wheat and Barley. (5th October 2015) - de San Celedonio, R. P.; Abeledo, L. G.; Brihet, J. M.; Miralles, D. J.
Abstract: The aim of this study was to analyse (i) the crop attributes that determine flowering time (i.e. final leaf number, FLN; and phyllochron, Phy), (ii) the dynamics of tiller appearance and (iii) the synchrony between leaf and tiller appearance in wheat and barley plants exposed to waterlogging. Two experiments were carried out in pots, in which wheat and barley cultivars were exposed to five waterlogging treatments, during different periods throughout the crop cycle, from emergence to maturity. The appearance of leaves and tillers on the main stem was measured twice a week in labelled plants. Waterlogging from emergence to flag leaf appearance significantly delayed time to flowering. The delay was greater when waterlogging occurred at the beginning of tillering, lengthening the period from emergence to flowering 24 % (13–15 days) in barley and 10–15 % (6–10 days) in wheat, as compared to control. Phy was the main attribute explaining the delay in flowering, as FLN was not altered. Waterlogging during the early stages of development reduced tiller appearance rate (TAR) in both species, but this effect was partially counterbalanced by a lengthening of the tillering phase, so the effect on final tiller number at maturity was limited. In conclusion, the exposure of wheat and barley to waterlogging during early stages of development delayed time to flowering and reduce TAR in both species. Waterlogging during more advanced crop stages produced slight effects on tillering dynamics, which would indicate that waterlogging affected structure generation more than mortality.